THE NEW TOOLS OF MANAGEMENT WITHIN PUBLIC INSTITUTIONS MOROCCANS- CASE OF THE BUDGETARY PROGRAMMING TRIENNALE- - EL OUD, Rachid; AMEDJAR , Abderrahim (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Following the adoption of the new organic law relating to the Finance Act of 2015, the purpose of this Article is to examine the new directions taken by Morocco for the improvement of the public governance, while focusing on the introduction of a new management system based on the measurement and evaluation of performance. Of this fact, our research has for objective:  To identify the new tools introduced in the management and in the audit of public expenditure;  And to analyze the new variables introduced in the management of public organizations.